Gaya Komunikasi Pimpinan dalam Memotivasi Karyawan di Perusahaan Consumer Goods - Ni, Chien; Oktavianti, Roswita (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
A company or organization needs a leader who is responsible for work motivation and employee performance. The right communication style will motivate someone to be able to excel, whether the employee is successful or not at work. PT XYZ is a consumer goods company that pays great attention to maintaining the motivation of its employees. This study uses several theories, namely communication theory, organizational communication, leadership communication style and motivation. This research uses a descriptive method. To complete this research, conducted in-depth interviews with three informants, namely the CEO of the learning & development division, the head of managerial leadership development and the head of functional development. And also the researcher conducted cross-interviews with triangulation of sources who were subordinates to the informants. This research concludes that the communication style applied in the Learning & Development Division of PT XYZ is a decentralized and democratic style. This communication style leads to The Equalitarian Style. Leaders in this division provide opportunities for every employee to express ideas and opinions in a relaxed manner. Suatu perusahaan atau organisasi membutuhkan seorang pemimpin yang bertanggung jawab dalam memberikan motivasi kerja dan menilai kinerja karyawan. Gaya komunikasi yang tepat akan memotivasi seseorang untuk dapat berprestasi, dan menentukan keberhasilan karyawan dalam bekerja. PT XYZ merupakan salah satu perusahaan consumer goods yang memiliki atensi tinggi dalam menjaga motivasi kayawannya. Penelitian ini menggunakan teori komunikasi, komunikasi organisasi, gaya komunikasi pimpinan dan motivasi. Penelitian ini merupakan metode penelitian deskriptif. Peneliti melakukan wawancara mandalam kepada tiga narasumber yaitu CEO divisi learning & development, head of managerial leadership development, dan head of functional development. Peneliti melakukan wawancara silang dengan triangulasi sumber yang merupakan bawahan dari narasumber tersebut. Penelitian ini disimpulkan bahwa gaya komunikasi yang diterapkan di Divisi Learning & development PT XYZ adalah gaya desentralisasi dan demokrasi. Gaya komunikasi ini mengarah pada The Equalitarian Style. Pimpinan dalam divisi ini memberikan kesempatan kepada setiap karyawan dapat mengungkapkan ide dan pendapat secara rileks.